The Effectiveness of Olson Couples Enrichment on Couples\' Marital Intimacy - Farahnaz Nazari; Ozra Etemadi; Ahmad Aabedi (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2019)
Aim and Background: Intimacy is a key and important property of a marital relationship and a distinguished attribute of a successful marriage. The purpose of the present study was to investigate the effectiveness of the couple relationship enrichment by Olson’s method on the increase in the marital intimacy of couples.